Industrial Energy Management and Sustainability - Benedetti, Miriam; Introna, Vito (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Growing environmental concerns caused by increasing consumption of naturalresources and pollution need to be addressed. Manufacturing dictates the efficiencywith which resource inputs are transformed into economically valuableoutputs in the form of products and services. Consequently, it is also responsiblefor the resulting waste and pollution generated from this transformation process.As a matter of fact, about one-third of the global total energy consumption isassociated withmanufacturing activities; thus, achieving higher energy efficiencyin this sector has been the focus of research as well as of policy and industrialprogrammes in recent years. In particular, being able to effectively manageenergy and energy-related activities has proved to be a fundamental capabilityfor companies willing to improve their sustainability, as it constitutes the first,critical step to understanding their processes and to identifying and correctlyevaluating improvement opportunities.This Special Issue focuses on energy management and sustainability of bothmanufacturing processes and systems, including methods, practices, tools, applicationsand experiences.